Tindakan Perompakan Di Laut Dalam Perspektif ASEAN - Celine Elisabeth Jenny Latusia (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: This study discusses acts of piracy that still occur in waters in various countries, especially in the Southeast Asian region. The International Chamber of Commerce's International Maritime Bureau notes that pirate attacks on ships in Southeast Asian waters are increasing sharply. Meanwhile, articles 100-107 of the United Convention On the Law Of The Sea 1982 (UNCLOS 1982) provide a framework for suppressing piracy under international law. So it is necessary to study the regulation of cooperation in International Legal Instruments and examine ASEAN countries to cooperate in dealing with acts of piracy at sea.Purposes of the Research: To study and know the arrangements regarding international cooperation regulated in International Law. To study and find out that ASEAN countries have collaborated in dealing with piracy at sea.Methods of the Research: The method used in this research is the type of normative juridical research method, the type of descriptive analytical research, the source of legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. Legal Material Analysis and Legal Material Analysis Methods.Results of the Research: The results of this study indicate that the arrangements for international cooperation between countries in International Legal Instruments are contained in article 13 of the United Nations Charter. International cooperation is also carried out based on provisions that have been agreed upon by the cooperating countries. Currently, there are two international treaties that regulate acts of piracy, namely the United Nations Convention on the Law of the Sea 1982 and the Convention for the Suppression of Unlawful Acts Against the Safety of Maritime Navigation 1988. There are several international organizations that regulate piracy including the International Maritime Organization, International Maritime Bureau, and for the Southeast Asia region, the ASEAN Maritime Forum as a form of realization of the ASEAN political-security community blueprint which serves as a dialogue forum to discuss appropriate steps against maritime threats such as piracy and piracy.